Is the Influence of Freud Declining in Psychology and Psychiatry? A Bibliometric Analysis - Yeung, Andy Wai Kan (Frontiers in Psychology, 2021)
Sigmund Freud is occasionally perceived as outdated and his work no longer relevant to the academia. The citing papers (CPs) that cited Freud works were collected from Web of Science and analyzed. The ten most common research areas of the CPs were noted, and the overall volume of the respective bodies of literature were retrieved. I computed the annual ratio of the respective bodies of literature that cited Freud. On a separate note, I computed the annual ratio of citations coming from psychology and psychiatry. Results based on 42,571 CPs found that psychology accounted for over half of the citations to Freud. The ratio of psychology papers citing Freud declined gradually from around 3% in the late 1950s to around 1% in the 2010s, in an extent of -0.02% per year over the entire survey period spanning across 65 years from 1956 till 2020 (P < 0.001). In psychiatry, a similar decline was observed, from around 4–4.5% in the late 1950s to just below 0.5% in the 2010s, in an extent of -0.1% per year (P < 0.001). However, a reverse trend was observed for psychoanalysis literature, which generally increased from 10–20% before the 1980s to 25–30% since the 2000s, in an extent of +0.2% per year (P < 0.001). Meanwhile, the annual ratio of CPs coming from psychology and psychiatry was decreasing by 0.4% per year (P < 0.001). Bibliometric data supported the notion that Freud’s influence was on a decline in psychology and psychiatry fields.